2022
DOI: 10.3389/fpsyt.2022.884600
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometrics analysis and visualization of autism spectrum disorder

Abstract: BackgroundThe prevalence of autism spectrum disorder (ASD) increased rapidly in the last 20 years. Although related research has developed rapidly, little is known about its etiology, diagnostic marker, or drug treatment, which forces researchers to review and summarize its development process and look for the future development direction.MethodsWe used bibliometrics to analyze papers of ASD in the Web of Science from 1998 to 2021, to draw the network of authors, institutions, countries, and keywords in the AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…In this regard, we found that the current research hotspots of emotion regulation research are depression, borderline personality disorder, parenting, psychopathology, bipolar disorder, reappraisal, mindfulness, adolescent, rumination, suppression, prefrontal cortex, aging, aggression, self-regulation, rumination, well-being, post-traumatic stress disorder and autism spectrum disorder as shown in Figures 8 and 9. This finding is consistent with earlier studies (Guo et al, 2022;Rong et al, 2022;Wang et al, 2021;Baminiwatta and Solangaarachchi, 2021;Yeung, 2018) which reported that these research areas in the spectrum of emotion regulation are currently attracting a significant amount of attention from researchers and practitioners around the globe due to their potential impact and relevance. In addition to this, Figure 10 demonstrated the research trends of emotion regulation and disclosed that Covid-19, non-suicidal self-injury, psychological distress and intimate partner violence are the most recent research themes that emerged in the past few years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this regard, we found that the current research hotspots of emotion regulation research are depression, borderline personality disorder, parenting, psychopathology, bipolar disorder, reappraisal, mindfulness, adolescent, rumination, suppression, prefrontal cortex, aging, aggression, self-regulation, rumination, well-being, post-traumatic stress disorder and autism spectrum disorder as shown in Figures 8 and 9. This finding is consistent with earlier studies (Guo et al, 2022;Rong et al, 2022;Wang et al, 2021;Baminiwatta and Solangaarachchi, 2021;Yeung, 2018) which reported that these research areas in the spectrum of emotion regulation are currently attracting a significant amount of attention from researchers and practitioners around the globe due to their potential impact and relevance. In addition to this, Figure 10 demonstrated the research trends of emotion regulation and disclosed that Covid-19, non-suicidal self-injury, psychological distress and intimate partner violence are the most recent research themes that emerged in the past few years.…”
Section: Discussionsupporting
confidence: 92%
“…A review of such studies is presented here. Rong et al (2022) performed a bibliometric analysis in the field of autism spectrum disorder. A total of 40,597 papers were published between 1998 and 2021 and were extracted from the Web of Science (WoS) database.…”
Section: Literature Review and Identification Of Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous bibliometric study found that research on ASD in the past 20 years mainly focused on its etiology, including brain structure, images, psychology, genes and animal models [ 103 ]. From 1998 to 2009, the classification and research of ASD and its subtypes have made great progress [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the etiology research of ASD is mainly focused on developmental neuroimaging and genetics during this period [ 101 ]. Many key brain regions have been proved to be related to the occurrence and development of autism, such as the medial prefrontal cortex, temporal-parietal junction [ 103 ], which provide potential options for the future treatment of ASD. From 2010 to 2018, with the promotion of the fifth edition of ASD diagnostic criteria in 2013, the research on ASD subtypes has been reduced to a certain extent, and chromosome and gene detection technologies have been widely used in ASD, which promoted the development of cytogenetic diagnostic tests for developmental delay/intellectual disability, ASD, or multiple congenital anomalies [ 101 ].…”
Section: Discussionmentioning
confidence: 99%